EFFECT OF STANDARD INTERFERON AND RIBAVIRIN ON LEUKOCYTE COUNT - Jadoon, Shakeel Ahmad; Ahmed, Ashfaq; Jehangiri, Attique -ur-Rehman; Ahmad, Nasir (Journal of Ayub Medical College Abbottabad, 2015)
Background: Chronic Hepatitis C is a public health problems in Pakistan, with 4.5% population infected. It is amenable to antiviral treatment. The ojective of this study was to determine the effect of antiviral treatment on leukocytes count during the treatment of hepatitis C. Methods: In this descriptive case series sixty PCR positive Hepatitis C patients were included and were given standard interferon and ribavirin for a period of six months with a monthly follow up. Total leukocytes were measured at monthly interval to study change in their counts. Results: The mean of baseline leukocytes was compared with the average mean leukocytes of six months treatment, and a decrease of 1603.36/mm3 was observed (p=0.000). Conclusion: Six months treatment of chronic hepatitis C with standard interferon and ribavirin decreases leukocytes count to a significant level. Keywords: Hepatitis C, Interferon, Ribavirin